2024
DOI: 10.3389/fbioe.2024.1355915
|View full text |Cite
|
Sign up to set email alerts
|

A putative design for the electromagnetic activation of split proteins for molecular and cellular manipulation

Connor J. Grady,
E. Alejandro Castellanos Franco,
Jory Schossau
et al.

Abstract: The ability to manipulate cellular function using an external stimulus is a powerful strategy for studying complex biological phenomena. One approach to modulate the function of the cellular environment is split proteins. In this method, a biologically active protein or an enzyme is fragmented so that it reassembles only upon a specific stimulus. Although many tools are available to induce these systems, nature has provided other mechanisms to expand the split protein toolbox. Here, we show a novel method for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…It is possible that this particular mutation affected the protein’s kinetics by altering the spacing and/or flexibility of the F residues in the 3F motif. This coincides with the theory that EPG undergoes a conformational change upon activation [ 18 ], where certain amino acids may produce more favourable conditions to allow this shift in confirmation.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…It is possible that this particular mutation affected the protein’s kinetics by altering the spacing and/or flexibility of the F residues in the 3F motif. This coincides with the theory that EPG undergoes a conformational change upon activation [ 18 ], where certain amino acids may produce more favourable conditions to allow this shift in confirmation.…”
Section: Resultssupporting
confidence: 89%
“…EPG is a small (~9 kDa) protein that adopts a Ly6/UPAR three-finger structure and is membrane associated via glycosylphosphatidylinositol (GPI) anchor [15]. EPG has shown response to magnetic stimuli in mammalian cells in the form of increased intracellular calcium [12,[15][16][17], in activatable split protein systems [18] and in rat models with increased neuronal plasticity [19] and reduced seizure activity [20], but its mechanism of action remains elusive. Site-directed mutagenesis has indicated a region of interest-the three-phenylalanine (3F) motif-in the protein that is essential for its function [15], but it remains unclear how this region facilitates magnetoreception.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetogenetics has been deployed to activate enzymes in E. coli and mammalian cells. Notable examples of this technology include the creation of a split NanoLuc, a split Peroxidase and a split version of the theranostic gene HSV1-TK [189]. Upon stimulation with an electromagnetic field, it was demonstrated that the EPG split HSV1-TK can kill 4T1-Luc2 cancer cells in culture in the presence of the prodrug ganciclovir.…”
Section: Challengementioning
confidence: 99%